The scapegoat sacrifice in Leviticus 16 and the Nefo'o ritual of the Bafut of Cameroon - Muyo, Joshua Ngwalem (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2001